How quickly do CEOs become obsolete? Industry dynamism, CEO tenure, and company performance - Henderson, Andrew D.; Miller, Danny; Hambrick, Donald C. (Strategic Management Journal, 2006)
Abstract Scholars have characterized CEO tenures as life cycles in which executives learn rapidly during their initial time in office, but then grow stale as they lose touch with the external environment. We argue, however, that the opportunities for adaptive learning are limited because (1) a CEO assumes office with a relatively fixed paradigm that changes little thereafter; (2) inertia limits the speed at which an organization can align itself with a new CEO's paradigm; and (3) for any within‐paradigm learning to occur, the external environment must be stable enough so that the cause–effect relationships that CEOs glean today remain relevant tomorrow. In a longitudinal study of 98 CEOs in the relatively stable branded foods industry and 228 CEOs in the highly dynamic computer industry, we found results that strongly supported our hypotheses. In the stable food industry, firm‐level performance improved steadily with tenure, with downturns occurring only among the few CEOs who served more than 10–15 years. In contrast, in the dynamic computer industry, CEOs were at their best when they started their jobs, and firm performance declined steadily across their tenures, presumably as their paradigms grew obsolete more quickly than they could learn. Copyright © 2006 John Wiley & Sons, Ltd.